(untitled) (Revista Latinoamericana de Derechos Humanos, 2014)
Las interceptaciones telefónicas son una clave para la instrucción del Proceso Penal, pero los riesgos a la colectividad son inmensurables ante un gobierno cada vez más policial y el sensacionalismo de los medios de comunicación. El Estado, cuando más grande, empieza en limitar los derechos fundamentales, teniendo como primero menester restringir la libertad persona, así como retrata George Orwell en su novela 1984. Abstract Wiretaps, to intercept telephone calls, are a very common key by the Criminal Procedure in the Ruleof Law. However, the risks for people are immensurable. Even the interceptions are increasing, thestates are getting more invasive by the civil rights and these facts contribute for the sensationalism ofthe press. The State, once bigger, starts to restrict the access to the civil rights, and the first actionis the restrictions to the rights of the free person, like the liberty of circulation, like George Orwellportrays in his novel, “1984”. Keywords freedom; wiretaps; law enforcement state; press; right to be alone; privacy.